TAKRIF GOOD PUBLIC GOVERNANCE PADA ASET BERSEJARAH MAKASSAR DAN GOWA - Namla Elfa Syariati (Jurnal Ilmiah Akuntansi Peradaban, 2021)
The application of Good Public Goernnce to historic assets to be able to present reports that are more transparent in the management of public goods (public goods), because they are included in public assets so that they are an important component in government. Especially historic assets with unique characteristics and have very high value at Fort Somba Opu Gowa and Fort Rotterdam Makassar. This research is included in the qualitative research by conducting interviews with informants at the Cultural Heritage Preservation Center (BPCB) and the South Sulawesi Provincial Culture and Tourism Office whether it is in accordance with the Accounting Standards in PSAP no 7 of 2010. Based on the research that has been conducted, it was found that BPCB Sulsel's historical assets Fort Rotterdam did not carry out any valuation either using acquisition value or revaluation, this was due to the absence of a policy from the Ministry to conduct an assessment of Fort Rotterdam's historic assets. Unlike the Tourism of the South Sulawesi Province which is responsible for Fort Somba Opu Gowa in its recognition, assessment and financial reporting is in accordance with PSAP 7 of 2010 Keywords: Good Public Governance, Accounting, Historical Assets, Financial Statements